1990
DOI: 10.1002/ajh.2830350104
|View full text |Cite
|
Sign up to set email alerts
|

Desferrioxamine improves neutrophil phagocytosis in thalassemia major

Abstract: The aims of the present study are: first, to assess the toxic role of serum from thalassemic patients in phagocytosis of PMN from healthy controls, and second, to seek to determine whether serum and cellular disturbances of polymorphonuclear neutrophils (PMN) phagocytosis, observed in thalassemic patients, can be prevented and/or corrected by use of desferrioxamine (DFX). Two kinds of in vitro incubations--without or with DFX--were performed. PMN or serum from thalassemic patients or from healthy controls was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…In the present study, we demonstrated that the addition of deferoxamine to cell cultures improved phagolysosomal fusion in TM patients. This is in accordance with other authors who showed that deferoxamine, at similar concentrations, en hanced the in vitro phagocytic function of human neutro phils [30,31]. Moreover, Speer et al [32] demonstrated that neutrophil function of children treated with deferox amine was similar to normal controls, suggesting that de feroxamine in vivo could improve neutrophil dysfunction, though they did not include in their study children without chelation therapy.…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, we demonstrated that the addition of deferoxamine to cell cultures improved phagolysosomal fusion in TM patients. This is in accordance with other authors who showed that deferoxamine, at similar concentrations, en hanced the in vitro phagocytic function of human neutro phils [30,31]. Moreover, Speer et al [32] demonstrated that neutrophil function of children treated with deferox amine was similar to normal controls, suggesting that de feroxamine in vivo could improve neutrophil dysfunction, though they did not include in their study children without chelation therapy.…”
Section: Discussionsupporting
confidence: 77%
“…Our results indicate that thalassaemia PMN contain higher levels of ROS than normal PMN and a lower ability to respond to PMA activation, suggesting an impaired bactericidal activity. The results also show that the oxidants studied, including iron and haemin, which are elevated in the plasma of thalassaemic patients (Cantinieaux et al , 1990), increase the ROS of PMN and reduce the response to PMA by respiratory burst. In contrast, antioxidants reduced ROS, but increased the ability of PMN to response to PMA.…”
mentioning
confidence: 60%
“…The mechanism is unclear, but it is possible that one or more components of the ROS generating system is damaged or consumed as a result of the chronic oxidative stress of the cells. We managed to recapitulate this situation in normal PMN by treatment with various oxidants, including iron and haemin, which are known to be high in thalassaemic patients (Cantinieaux et al , 1990). Most of these patients suffer from iron‐overload (in spite of chelation therapy) because of increased dietary iron absorption and frequent therapeutic blood transfusions.…”
Section: Discussionmentioning
confidence: 99%
“…Impairments of phagocyte functions such as chemotaxis, phagocytosis, and intracellular killing have been detected more commonly and consistently than the defects of other host defenses in thalassemia patients (35,38,39). Phagocyte dysfunctions seem to be associated with iron overload (35,38),and their improvement can be demonstrated by desferrioxamine (40).…”
Section: Phagocyte Dysfunctionmentioning
confidence: 99%